Extension of the franchise to women in Zanzibar - Great Britain; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1959)
Government memoranda, with ms. annotations, relating to the enfranchisement of women in preparation for the 1960 Zanzibar elections